2017
DOI: 10.1159/000455061
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hemodynamic Instability and Fluid Overload are Associated with Increasing Acute Kidney Injury Severity and Worse Outcome after Cardiac Surgery

Abstract: Purpose: The study aimed to investigate patients' characteristics, fluid and hemodynamic management, and outcomes according to the severity of cardiac surgery-associated acute kidney injury (CSA-AKI). Methods: In a single-center, prospective cohort study, we enrolled 282 adult cardiac surgical patients. In a secondary analysis, we assessed preoperative patients' characteristics, physiological variables, and medication for intra- and postoperative fluid and hemodynamic management and outcomes according to CSA-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 24 publications
1
43
0
1
Order By: Relevance
“…Expressed in many organs such as heart, lung, liver, and intestines, and is an independent predictor of postoperative renal dysfunction -Preoperative detection -Superior predictive ability compared to risk scores such as EuroSCORE -Marker is also associated with mortality and morbidity, hence, association with AKI might not independent AKI=acute kidney injury; CCABs=cell-cycle arrest biomarkers; CKD=chronic kidney disease; CSA-AKI=cardiac surgery-associated acute kidney injury is a summary of the key studies comparing both solution types. Perioperative fluid overload is also associated with increased severity of AKI and increased mortality post cardiac surgery [42] . In a recent study by Bhaskaran et al [43] , they found out that perioperative use of chloride-restricted intravenous fluids is associated with statistically significant lower incidence of AKI stage I, whilst chloride-liberal intravenous fluids are associated with hypochloremia acidosis and increased incidence of AKI stage I post CABG.…”
Section: E Fluid Managementmentioning
confidence: 99%
“…Expressed in many organs such as heart, lung, liver, and intestines, and is an independent predictor of postoperative renal dysfunction -Preoperative detection -Superior predictive ability compared to risk scores such as EuroSCORE -Marker is also associated with mortality and morbidity, hence, association with AKI might not independent AKI=acute kidney injury; CCABs=cell-cycle arrest biomarkers; CKD=chronic kidney disease; CSA-AKI=cardiac surgery-associated acute kidney injury is a summary of the key studies comparing both solution types. Perioperative fluid overload is also associated with increased severity of AKI and increased mortality post cardiac surgery [42] . In a recent study by Bhaskaran et al [43] , they found out that perioperative use of chloride-restricted intravenous fluids is associated with statistically significant lower incidence of AKI stage I, whilst chloride-liberal intravenous fluids are associated with hypochloremia acidosis and increased incidence of AKI stage I post CABG.…”
Section: E Fluid Managementmentioning
confidence: 99%
“…The rise in serum creatinine levels in cardiac patients prior to surgery might explain persistent hypertension and subclinical inflammation derived from atherosclerotic endothelial dysfunction accompanied by cardiovascular diseases that initially upsets renal function [22]. While the deleterious influences of some anesthetics [23], catheterization used in critically ill patients [24], and the circulatory pump machine probably result in fluid overload [25], low blood viscosity [26], hemodilution anemia [27], microembolism [28], tissue hypoperfusion [29], hypothermia [30], and hypotension due to the low cardiac output lead to exaggerated elevations of intra-and postoperative levels [31]. In a related context, CRP levels increased massively after surgery in the AKI versus the non-AKI group, indicating the presence of localized inflammation as one of the heart-lung machine adverse effects [32].…”
Section: Discussionmentioning
confidence: 99%
“…Positive cumulative fluid balance caused by excessive fluid administration during the perioperative phase is known as one of the most common clinical complications in post-intensive care unit cardiac surgery patients 1. Mostly, administration of diuretics is initiated to correct the fluid overload.…”
Section: Descriptionmentioning
confidence: 99%